In Vitro Study of Phytochemistry and Nutritional Status of Anthocleista vogelii - Augustine, Apiamu; Samuel O, Asagba; Tonukari , Nyerhovwo J; Obiwulu , Esther (Nigerian Journal of Pharmaceutical and Applied Science Research, 2017)
To ascertain the nutritional and phytochemical contents of the leaf samples of Anthocleista vogelii. The plant samples after pulverization were subjected to maceration method, which were analysed for proximate, phytochemicals and mineral contents using standard procedures. The proximate analysis indicated a significant amount of its nutrients with the exception of moisture content in dry leaf samples of A. vogelii, which was evident in their energy content of 329.96 ± 0.88 kcal.100 g of sample than the fresh leaf sample with an energy content of 282.32 ± 0.36 kcal/100 g of sample respectively. The plant leaves revealed that with the exception of sodium mineral, the dry leaf samples constituted a higher significant amount of macro- and micronutrients, (Na, K, Ca, Mg, P, Fe, Zn, Mn and Cr), than the fresh samples, but the latter revealed the nutritional mark of preference in view of their Ca/P and Na/K ratios respectively. The phytochemical screening showed the presence of alkaloids, flavonoids, saponins, tannins, steroids, phenolics and anthraquinones, which were quantitatively elucidated with considerable preference for the dry sample compared to the fresh sample. It may be inferred in this study that in terms of Na/K and Ca/P ratios, the fresh use of A. vogelii is nutritionally suggested, the traditional use of the dry plant in terms of their bioactive compounds may be recommended for therapeutic efficacy and the use of the plant regardless of its form for antioxidant supplementation to ameliorating oxidative stress may be of essence in toxicant-induced oxidative damage during in vivo studies.